ANALISIS NILAI SOSIAL PADA TRADISI MERON PATI DALAM CERITA RAKYAT KARYA KANZUNUDDIN - Maharani, Titis Puspita; Amalia, Indi; Parasdika, Nayala Intani; Kanzunnudin, Mohammad (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aims to analyze the social value of Axel Olrix's narrative structure in the story of the Meron tradition in Sukolilo, Pati, Central Java in Kanzunnudin's East Coast folklore. The Meron tradition is a celebration of the Prophet Muhammad's birthday that is full of local cultural meanings. With a descriptive qualitative approach, data were taken from Kanzunnudin's work entitled “East Coast Folklore” and analyzed through reduction, presentation, and conclusion drawing. The results show that this story contains the value of leadership, mutual cooperation, religiosity, cultural preservation, and collective identity of the community. Axel Olrix's narrative structure also follows typical oral patterns such as clear opening-closing, strong main character, repetition, and contrast. These findings confirm that folktales such as Suro Kadam function as a tool for social value education as well as a reinforcement of the community's cultural identity. Its preservation is important to maintain the continuity of local traditions and characters.